Optimal upper gastrointestinal surveillance strategies for gastric, small bowel and pancreatic cancer detection in Lynch syndrome - Tim Marwitz; Aleksander M. Bogdanski; Robert Hüneburg; Monique E. van Leerdam (Familial Cancer, 2026)
Lynch syndrome is an autosomal dominant cancer predisposition syndrome and the most common cause of hereditary colorectal cancer. In addition to colorectal cancer, it confers substantially increased risks for several extracolonic malignancies. While there is broad consensus regarding the effectiveness of endoscopic colorectal surveillance, recommendations for surveillance of gastric, small bowel, and pancreatic cancers vary considerably among guidelines issued by leading professional societies. These discrepancies largely reflect the limited availability of robust, high-quality evidence. In this narrative review, we summarize the cancer risks for gastric, small bowel, and pancreatic malignancies in Lynch syndrome carriers, discuss recent studies evaluating the outcomes of surveillance strategies, and provide an overview of current guideline recommendations. Furthermore, we highlight emerging approaches that may enhance surveillance strategies in the future. In recent years, increasing research efforts have focused on surveillance for less frequent Lynch syndrome-associated malignancies, however, prospective data from large, well-characterized cohorts remain scarce. Such data are essential to harmonize existing guidelines and to enable the development of personalized surveillance strategies for individuals affected by Lynch syndrome.

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.